STUDI PENINGKATAN KESIAPAN GURU SEKOLAH DASAR DALAM PENYUSUNAN RPP IMPLEMENTASI KURIKULUM 2013 - I Ketut Ngurah Ardiawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This study consists of compilation of information from the literatures and researcheson teacher preparedness in creating lesson plan which implement Curriculum 2013. This methodis called